2013
DOI: 10.1016/j.humimm.2013.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Down-regulation of CD5 expression on activated CD8+ T cells in familial hemophagocytic lymphohistiocytosis with perforin gene mutations

Abstract: Hemophagocytic lymphohistiocytosis (HLH) is characterized by uncontrolled activation of T cells and macrophages with overproduction of cytokines. Familial HLH type2 (FHL2) is the most common form of primary HLH and is caused by mutations in PRF1. We have recently described a significant increase in the subpopulation of CD8 + T cells with clonal expansion and CD5 down-regulation in Epstein-Barr virus associated-HLH, which represented a valuable tool for its diagnosis. However, this unusual phenotype of CD8 + T … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
32
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 21 publications
5
32
0
Order By: Relevance
“…More importantly, a significant increase in the subpopulation of activated CD8 + T cells with downregulation of CD5 expression was demonstrated in the patient. These findings are similar to those of FHL2 . While the mechanism underlying downregulation of CD5 on activated CD8 + T cells remains to be elucidated, it is tempting to speculate that patients with any of the FHL subtypes other than FHL2 might also have downregulation of CD5 on activated CD8 + T cells during the acute phase.…”
Section: Discussionsupporting
confidence: 64%
See 3 more Smart Citations
“…More importantly, a significant increase in the subpopulation of activated CD8 + T cells with downregulation of CD5 expression was demonstrated in the patient. These findings are similar to those of FHL2 . While the mechanism underlying downregulation of CD5 on activated CD8 + T cells remains to be elucidated, it is tempting to speculate that patients with any of the FHL subtypes other than FHL2 might also have downregulation of CD5 on activated CD8 + T cells during the acute phase.…”
Section: Discussionsupporting
confidence: 64%
“…It has recently been reported that CD5 is recruited and co‐localized with CD3 at the immunological synapse and inhibits T‐cell receptor (TCR) signaling in T cells without interfering with immunological synapse formation . In this report, we extended our previous observation and investigated a patient with FHL3 who had downregulation of CD5 on activated CD8 + T cells.…”
mentioning
confidence: 57%
See 2 more Smart Citations
“…CD5 − status has been suggested to be an adverse prognostic factor (30), and the downregulation of CD5 expression in EBV-HLH has been reported to be associated with the serum levels of cytokines, and T cell activation and proliferation (31). In the present study, the IPI scores of CD5 − patients were clearly higher than those in CD5 + patients, and the mean survival time of CD5 − patients was shorter; moreover, an association between CD5 expression and OS was identified.…”
Section: Discussionmentioning
confidence: 99%